Efficiency of β-glucan utilisation in fish culture - Hoang, Do Huu (Vietnam Journal of Marine Science and Technology, 2019)
In the last three decades aquaculture is a rapidly developing sector worldwide and antibiotics are used popularly as growth promoter. Antibiotic use was banned because research proved that antibiotic has caused many effects on environment and human health. Therefore, finding antibiotic alternatives is the first priority. The most prospect products today are probiotic and prebiotic. β-glucan is one of the immunostimulants which showed a variety of benefits to the health of many aquaculture species. In this paper only the results of β-glucan, a kind of prebiotic supplied in aquaculture, were summarized. The major benefit of β-glucan are to boost growth, to reduce mortality, to enhance tolerance or stress resistance to environmental or pathogen challenges. Although the applications of β-glucan are popular worldwide, its use in aquaculture in Vietnam is still limited. This paper provides an important reference for β-glucan utilisation which may help to develop a sustainable aquaculture in Vietnam.